2005
DOI: 10.3354/dao063205
|View full text |Cite
|
Sign up to set email alerts
|

Revision of Myxobolus heterosporus Baker, 1963 (syn. Myxosoma heterospora) (Myxozoa: Myxosporea) in African records

Abstract: There is uncertainty regarding the validity of Myxobolus heterosporus Baker, 1963. The present study revises the taxonomy, using specimens isolated from plasmodia situated in the infected cornea of Oreochromis aureus, O. niloticus or Tilapia zillii inhabiting the River Nile, Egypt. In addition, histological effects of the parasite on the infected tissue were examined. The spores of M. heterosporus had a variety of shapes expressing remarkable heteromorphism. Five main Myxobolus-like spore types and tailed-spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
2
4
0
1
Order By: Relevance
“…A piece of evidence that provides support for this theory is the occurrence of some Myxobolus spp. that develop spores both with and without a Henneguya -like caudal prolongation within a single plasmodium, as reported for Myxobolus turpisrotundus Liu et al, 2010 [19], Myxobolus bizerti Bahri and Marques, 1996, Myxobolus mulleri Bahri, 1997 and Myxobolus heterosporus Baker, 1963 [55].…”
Section: Discussionsupporting
confidence: 60%
“…A piece of evidence that provides support for this theory is the occurrence of some Myxobolus spp. that develop spores both with and without a Henneguya -like caudal prolongation within a single plasmodium, as reported for Myxobolus turpisrotundus Liu et al, 2010 [19], Myxobolus bizerti Bahri and Marques, 1996, Myxobolus mulleri Bahri, 1997 and Myxobolus heterosporus Baker, 1963 [55].…”
Section: Discussionsupporting
confidence: 60%
“…Bahri (2008) reported on this in Myxobolus bizerti and Myxobolus mülleri spores with caudal appendages. El-Mansy (2005) also observed the same phenomena in Myxobolus heterosporus and demonstrated that tailed-spores might be heteromorphs of this species. Shulman (1966) dedicated significant discussion to atypical spores of Myxobolus kawabatae and Myxobolus gigi that also possess these variable appendages.…”
Section: Discussionsupporting
confidence: 53%
“…2). Given these findings and earlier observations on Myxobolus species with Henneguya-like tails (Shulman 1966;El-Mansy 2005;Bahri 2008), the caudal projections are clearly a trait that many of these species have the genetic capacity to express. Alternatively, this is a convergent trait having arisen multiple times in the evolution of the myxobolids.…”
Section: Discussionmentioning
confidence: 70%
“…Myxobolus spores with caudal appendages have been reported in several previous studies (Shulman 1966, Bahri 2008, El-Mansy 2005, Liu et al 2010a, 2014a, indicating that species of Myxobolus have the genetic capacity to develop Henneguya-like caudal appendages, and the caudal appendages may not be a valid character to distinguish Myxobolus with Henneguya. Tissue tropism was found to be an important feature for general clustering of myxozoans (Fiala 2006, Carriero et al 2013, Shin et al 2014, but this trend was not observed for clustering of species within the Myxobolus clade in the present study.…”
Section: Discussionmentioning
confidence: 98%